A Case Report of Multiple Gastrointestinal Stromal Tumors: Imaging Findings, Surgical Approach, and Review of the Literature - Tarallo, Mariarita; Carruezzo, Cristina; Dentice Di Accadia, Filippo Maria; Del Gaudio, Antonella; Caruso, Damiano; Polici, Michela; Crocetti, Daniele; Costi, Umberto; Polistena, Andrea; Panzuto, Francesco; Laghi, Andrea; Cavallaro, Giuseppe; et al. (Frontiers in Surgery, 2022)
Introduction: Multiple gastrointestinal stromal tumors (GISTs) are rare tumors. Differential diagnosis between metastatic and multiple GISTs represents a challenge for a proper workup, prediction prognosis and therapeutic strategy. Case presentation: We present a case of 67-year-old man with CT evidence of multiple exophytic lesions in abdomen, reaching a diameter from 1- to 9-cm, without any signs of organs infiltration and resulted positive at 18F-FDG-PET/CT. Laparoscopic biopsy revealed multiple GIST, and surgical resection by using an open approach was performed to reach radicality. Moreover, an extensive review of the current literature was performed. Results: Small GISTs (<5cm) can be treated by laparoscopic approach while in case of large GISTs (>5cm), tumor location and size should be taken into account to reach radical surgery avoiding tumor rupture. For metastatic GISTs Imatinib represents the first choice of treatment, and surgery should be considered only in few selected cases when all lesions are resectable. Conclusions: Sporadic multiple GISTs are a rare event, imaging findings are not specific of GIST and the biopsy needs for a secure diagnosis and proper management. In case of large lesions, with high risk of vessels injury, laparotomy excision should be considered to achieve radicality and to avoid tumor rupture.